2021
DOI: 10.3390/app11136161
|View full text |Cite
|
Sign up to set email alerts
|

Mushroom Ligninolytic Enzymes―Features and Application of Potential Enzymes for Conversion of Lignin into Bio-Based Chemicals and Materials

Abstract: Mushroom ligninolytic enzymes are attractive biocatalysts that can degrade lignin through oxido-reduction. Laccase, lignin peroxidase, manganese peroxidase, and versatile peroxidase are the main enzymes that depolymerize highly complex lignin structures containing aromatic or aliphatic moieties and oxidize the subunits of monolignol associated with oxidizing agents. Among these enzymes, mushroom laccases are secreted glycoproteins, belonging to a polyphenol oxidase family, which have a powerful oxidizing capab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 170 publications
(256 reference statements)
0
9
0
Order By: Relevance
“…Furthermore, the degradation of organochlorides can be achieved by the synergistic action of enzymes and prooxidants, which are produced by the basidiomycetes, such as superoxide anion (O 2 − ), H 2 O 2 , hydroxyl radicals (-OH), and singlet oxygen ( 1 O 2 ). 27 The presence of HCB promoted the production of laccase isoforms by D. castanella with optimal pH and inhibition pattern typical of basidiomycetes, being the decrease in activity in presence of H 2 O 2 suggestive of absence of peroxidases in the brute extracts. 27,51,52 However, higher optimal temperatures were observed for D. castanella laccase when compared with the laccases produced by other basidiomycetes (55-60 • C), as well as higher thermostability, 52 thereby suggesting the applicability of this species and its enzymatic arsenal in the degradation of POP.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Furthermore, the degradation of organochlorides can be achieved by the synergistic action of enzymes and prooxidants, which are produced by the basidiomycetes, such as superoxide anion (O 2 − ), H 2 O 2 , hydroxyl radicals (-OH), and singlet oxygen ( 1 O 2 ). 27 The presence of HCB promoted the production of laccase isoforms by D. castanella with optimal pH and inhibition pattern typical of basidiomycetes, being the decrease in activity in presence of H 2 O 2 suggestive of absence of peroxidases in the brute extracts. 27,51,52 However, higher optimal temperatures were observed for D. castanella laccase when compared with the laccases produced by other basidiomycetes (55-60 • C), as well as higher thermostability, 52 thereby suggesting the applicability of this species and its enzymatic arsenal in the degradation of POP.…”
Section: Discussionmentioning
confidence: 94%
“…27 The presence of HCB promoted the production of laccase isoforms by D. castanella with optimal pH and inhibition pattern typical of basidiomycetes, being the decrease in activity in presence of H 2 O 2 suggestive of absence of peroxidases in the brute extracts. 27,51,52 However, higher optimal temperatures were observed for D. castanella laccase when compared with the laccases produced by other basidiomycetes (55-60 • C), as well as higher thermostability, 52 thereby suggesting the applicability of this species and its enzymatic arsenal in the degradation of POP. 33 Furthermore, these findings were also corroborated by other authors who observed the production of fungal laccases…”
Section: Discussionmentioning
confidence: 94%
“…The general procedure starting from 3-phenyl-salicylic aldehyde (6) (149 mg, 0.75 mmol) [108], 2-hydroxybenzohydrazide (16) (114 mg, 0.75 mmol), CH 3 OH (30 mL), and AcOH (75 µL) was employed with a 3.5 h reaction time and crystallization with concentration to obtain a white solid the 2-hydroxy-N -[(E)-(2-hydroxy-3-phenyl-phenyl)methylidene] benzohydrazide (4m) (206 mg, 0.62 mmol) with 83% yield, which melts in 224-227 J = 7.9 Hz, 4 J = 1.6 Hz, 1H, H-6), 7.61 (dd, 3 J = 8.1 Hz, 4 J = 1.2 Hz, 2H, PhH-2,6), 7.48 (dd, 3 J = 7.6 Hz, 4 J = 1.5 Hz, 1H, ArH-6), 7.47 (ddd, 3 J = 8.3 Hz, 3 J = 7.2 Hz, 4 J = 1.6 Hz, 1H, H-4), 7.45 (ddd, 3 J = 8.1 Hz, 3 J = 7.4 Hz, 2H, PhH-3,5), 7.41 (dd, 3 J = 7.5 Hz, 4 J = 1.5 Hz, 1H, ArH-4), 7.36 (tt, 3 J = 7.4 Hz, 4 J = 1.2 Hz, 1H, PhH-4), 7.06 (dd, 3 J = 7.6 Hz, 3 J = 7.5 Hz, 1H, ArH-5), 7.01 (dd, 3 J = 8.3 Hz, 4 J = 1.0 Hz, 1H, H-3), 6.98 (ddd, 3 J = 7.9 Hz, 3 J = 7.2 Hz, 4 J = 1.0 Hz, 1H, H-5) ppm; 13 (dd, 3 J = 7.9 Hz, 3 J =7.3 Hz, 2H, PhH-3.5), 7.40 (dd, 3 J = 7.6 Hz, 4 J = 1.4 Hz, 1H, ArH-4), 7.37 (t, 3 J = 7.9 Hz, 1H, PhH-4), 7.32-7.37 (m, 3H, H-2, H-5, H-6), 7.04 (dd, 3 J = 7.6 Hz, 3 J = 7.6 Hz, 1H, ArH-5), 7.02 (ddd, 3 J = 7.8 Hz, 4 J = 2.3 Hz, 4 J = 1.2 Hz, 1H, H-4) ppm; 13 The general procedure starting from 3-tert-butyl-5-methyl-salicylic aldehyde (8) (192 mg, 1.0 mmol) [108], 1-hydroxy-2-naphthohydrazide (19) (202 mg, 1.0 mmol) [109], CH 3 OH (65 mL), and AcOH (100 µL) was employed with a 6 h reaction time and concentrated by slow distillation before crystallization to obtain the colorless prisms of N -[(E)-(3-tert-butyl-2-hydroxy-5-methylphenyl)methylidene]-2-(1-hydroxynaphtho)hydrazide (5a) (345 mg, 0.916 mmol) with 92% yield, which melts at 215-217 3 J = 8.9 Hz, 1H, H-3), 7.92 (d, 3 J = 8.1 Hz, 1H, H-5), 7.69 (ddd, 3 J = 6.8 Hz, 3 J = 6.8 Hz, 4 J = 1.2 Hz, 1H, H-6), 7.62 (d, 3 J = 7.7 Hz, 2H, PhH-2,6), 7.60 (ddd, 3 J = 8.2 Hz, 3 J = 6.8 Hz, 4 J = 1.1 Hz, 1H, H-7), 7.53 (dd, 3 J = 7.7 Hz, 4 J = 1.4 Hz, 1H, ArH-6), 7.49 (d, 3 J = 8.9 Hz, H-4), 7.46 (dd, 3 J = 7.7 Hz, 3 J = 7.3 Hz, 2H, PhH-3,5), 7.43 (dd, 3 J = 7.5 Hz, 4 J = 1.4 Hz, 1H, ArH-4), 7.36 (t, 3 J = 7.3 Hz, 1H, PhH-4), 7.07 (t, 3 J = 7.7 Hz, 3 J = 7.5 Hz, 1H, ArH-5) ppm; 13 The general procedure starting from 3,5-di-tert-butyl-salicylic aldehyde (9) (234 mg, 1.0 mmol) [108], 1-hydroxy-2-naphthohydrazide (19) (202 mg, 1.0 mmol) [109], CH 3 OH (75 mL), and AcOH (100 µL) was employed with a 2 h reaction time, decolorization with charcoal and concentration slow by distillation before crystallization to obtain N -[(E)-…”
Section: -Hydroxy-n -[(E)-(2-hydroxy-3-phenyl-phenyl)methylidene]benzohydrazide (4m)mentioning
confidence: 99%
“…It has the exceptional ability to one electron oxidize both low-and high-molecular-weight substrates via direct or mediated reactions applied in green chemistry [1]. This nonspecific property has been reflected in numerous industrial, medical, and environmental applications [2][3][4][5]. Prokaryotes [6] and eukaryotes such as insects [7], plants, and fungi [8] produce laccase.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation